A prospective randomized study of three different methods of episiotomy repair - Uslu, M.A.; Ozekici, U.; Simsek, M.; Berkman, S. (My University, 1992)
[Abstract Not Available]
Keywords: polyglycolic acid; article; catgut; clinical trial; controlled study; disability; episiotomy; female; human; major clinical study; pain; pharmacology; puerperium; randomized controlled trial; silk; surgical technique